- The constitutional institutions activity in the mixed regime - a comparative study - between the constitution of France of 1958 and the permanent constitution of the Republic of Iraq of 2005 - Abdel-Hussein Abdullah, Lecturer, Dr. Azhar; Assist. Lecturer. Afnan Abdulhussein Abdullah, (The college of law and political science journal, 2023)
Democratic state structure must rely on various constituents that are conducive to consolidating the citizenship concept and people's equality. The activation of such constituents depends on the activity of the constitutional institutions of the state. Such institutions are not integral part of the government formation ; rather they are beyond government and they exist because the constitution has enacted them. They are accountable for interpreting the implications of the constitution whether it is related to law legislation, execution, implementation or applying them to disputes before specialised courts.     France Constitution of 1958 pointed out to the constitutional institutions and restricted them to the legislative power, executive power and the constitutional Council. Moreover, it was keen to strike a balance between the priliviges of both the legislative and the executive powers without converging to the national representation sovereignty and the government distabilzation.     Iraq permanent Constitution of 2005 refers on the other hand to the constitutional institutions and limited them to the legislative power, executive power, and legal power. It has authorised each institution to consider its move that should not go beyond the limit drawn by the constitution